(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Empowering students with literacy skills so that they can grow and compete in the global workforce can be achieved via a strong and robust educational system. However, in some third world countries including Pakistan, ready access to schools may not be a viable option for some students due to resource constraints or due to cultural or religious limitations. Innovative strategies to enhance literacy skills can have a significant impact in alleviating gaps between those students who are denied educational opportunities vis-à-vis privileged students who receive quality education, and several non-governmental organizations (NGOs) have taken creative steps to provide opportunities for children in remote parts of Pakistan to develop literacy skills and promote a reading culture. This paper will explore the results from a qualitative study on three NGOs and explain how they promote literacy for the most vulnerable populations.